Property rights and access : the case of community based fisheries management in Bangladesh - Md. Nurul Islam, Gazi; Tai, Shzee Yew (2012)
The complexity of property rights of inland fisheries in Bangladesh was due to the diverse physical characteristics of the water bodies and the multiple stakeholders. The revenue oriented management has failed to involve poor fishers into the fisheries management. A community-based fisheries management (CBFM) system was implemented to ensure fishing rights of the poor, improve productivity and sustainability of fisheries resources through joint action of the fishers. This study investigates the extent of fisher’s access to fishing in the various types of water bodies such as closed beels (deeper depressions in the floodplain), open beels (lake), rivers and floodplains to enhance their livelihoods. Data was obtained from a pair of questionnaire-based field surveys: a baseline study carried out in 2002 and an impact study carried out in mid-2006. A total 2826 households were interviewed comprising of 1994 households at 34 CBFM project water bodies and 832 households at 6 control water bodies were chosen in selected regions in Bangladesh. This study found that the CBFM fishers have obtained greater access to fisheries and improved livelihoods than non-CBFM fishers. The fishers have now changed their attitudes, have greater awareness of fisheries rules and are able to resolve conflicts much easier in the CBFM water bodies. Long term access rights over fisheries resources should thus be considered as the priority for a sustainable inland fishery and livelihoods of fishers in Bangladesh.